2022
DOI: 10.3389/fcell.2022.845567
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Role of Ependymal and Vascular Cells as Sources of Extracellular Cues Regulating the Mouse Ventricular-Subventricular Zone Neurogenic Niche

Abstract: Neurogenesis persists in selected regions of the adult mouse brain; among them, the ventricular-subventricular zone (V-SVZ) of the lateral ventricles represents a major experimental paradigm due to its conspicuous neurogenic output. Postnatal V-SVZ neurogenesis is maintained by a resident population of neural stem cells (NSCs). Although V-SVZ NSCs are largely quiescent, they can be activated to enter the cell cycle, self-renew and generate progeny that gives rise to olfactory bulb interneurons. These adult-bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Previously, we reported that TSK is secreted by ependymal cells, binds to frizzled three receptors, and regulates Wnt signaling. We hypothesized that the secreted TSK may affect Wnt signaling non-autonomously in the SVZ cells ( Ito et al, 2021 ; Quaresima et al, 2022 ). To investigate how TSK impacts GFAP + cells, we analyzed the localization of TSK in GFAP + cells by immunohistochemistry using monoclonal anti-TSK antibody (Mab1D3F1) .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that TSK is secreted by ependymal cells, binds to frizzled three receptors, and regulates Wnt signaling. We hypothesized that the secreted TSK may affect Wnt signaling non-autonomously in the SVZ cells ( Ito et al, 2021 ; Quaresima et al, 2022 ). To investigate how TSK impacts GFAP + cells, we analyzed the localization of TSK in GFAP + cells by immunohistochemistry using monoclonal anti-TSK antibody (Mab1D3F1) .…”
Section: Resultsmentioning
confidence: 99%
“…Since SFO tanycytes express the NSC marker Sox2 (Figure 3B), but do not undergo constitutive proliferation, they might represent a quiescent NSC pool. Previous studies in the SVZ and SGZ have demonstrated that NSC pools remain dormant until they are stimulated, inducing the quiescent NSCs to enter the cell cycle and start proliferating 56–58 . Injuries and pathological states can induce the transition of quiescent NSCs into proliferating NSCs 59–61 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the SVZ and SGZ have demonstrated that NSC pools remain dormant until they are stimulated, inducing the quiescent NSCs to enter the cell cycle and start proliferating. [56][57][58] Injuries and pathological states can induce the transition of quiescent NSCs into proliferating NSCs. [59][60][61] Future studies should elucidate if SFO tanycytes represent a quiescent NSC pool that can be stimulated and proliferate, generating new neurons and glia in physiological or pathological conditions.…”
Section: Ovlt and Sfo Represent New Adult Neurogenesis Areasmentioning
confidence: 99%
“…It is important to consider that, in the post-natal V-SVZ niche, the ependymal cells co-exist with qNSCs, RG progenitors, and NBs. Ependymal cells are ciliated structures that interact with ventricle fluid forming the vertical system, and may represent a dormant stem cell niche of endogenous NSCs (Quaresima et al, 2022 ). Transcriptional profiling from transgenic mice specifically targeting ependymal cells revealed a unique gene expression pattern of those cells despite they share some of the classical NSC transcriptional patterns (Shah et al, 2018 ).…”
Section: Profiling Of Enscs In the Physiological Environmentmentioning
confidence: 99%